An innovative approach to providing collaborative education to undergraduate students in the area of child maltreatment. Issue 3 (May 2015) - Johnson, Lisa
Abstract Frontline workers in the area of child welfare often enter the field without having taken any specialized coursework in the area of child maltreatment. This article discusses an interdisciplinary certificate program that is specifically designed to teach persons from various academic areas the knowledge and skills necessary to work with children who experience maltreatment. The child advocacy studies certificate program specifically focuses on coursework in the area of child maltreatment and child advocacy to better train future frontline workers in their vital roles. This certificate will decrease underreporting of child abuse cases by mandated reporters by making them more aware of the signs and symptoms of child maltreatment and also give students a greater understanding of how to work with individuals from various fields.